2019
DOI: 10.1103/physrevmaterials.3.075602
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity percolation control of the brittle-ductile transition in disordered networks

Abstract: In ordinary solids, material disorder is known to increase the size of the process zone in which stress concentrates at the crack tip, causing a transition from localized to diffuse failure. Here, we report experiments on disordered 2D lattices, derived from frictional particle packings, in which the mean coordination number z of the underlying network provides a similar control. Our experiments show that tuning the connectivity of the network provides access to a range of behaviors from brittle to ductile fai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…Combined with [36,37], our work provides evidence that betweenness centrality successfully identifies physical properties in both granular packings and lattices that are derived from them. Similarly, analyses inspired by rigidity percolation in granular materials have identified that our disordered lattices undergo a ductile-brittle failure transition as a function of connectivity z 0 , as determined by counting degrees of freedom and constraints [38]. However, we have focused on testing the sensitivity and specificity of our approach in the context of disordered lattices that we generated from force networks in quasi-2D granular packings, and this does not ensure its success for other network structures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Combined with [36,37], our work provides evidence that betweenness centrality successfully identifies physical properties in both granular packings and lattices that are derived from them. Similarly, analyses inspired by rigidity percolation in granular materials have identified that our disordered lattices undergo a ductile-brittle failure transition as a function of connectivity z 0 , as determined by counting degrees of freedom and constraints [38]. However, we have focused on testing the sensitivity and specificity of our approach in the context of disordered lattices that we generated from force networks in quasi-2D granular packings, and this does not ensure its success for other network structures.…”
Section: Discussionmentioning
confidence: 99%
“…As was reported in Berthier et al [38], one can control the compressive and tensile failure behaviors of a disordered lattice by tuning the mean degree of its associated network. This control parameter provides a way to create systems with a variety of failure behaviors, ranging from ductile-like to brittle-like failure.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations